2005
DOI: 10.1177/0898010105280097
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Nutraceutical Products Marketed for Cognitive and Memory Enhancement

Abstract: This article identifies a convenience sample of 14 memory-enhancing herbal products that were found to be available commercially, examines their active ingredients, states their claims, and evaluates the available evidence to determine their efficacy. The analyses identified four problematic areas. First, a majority of the products use cognitive terminology, which leads consumers to anticipate an intended cognitive benefit. Second, some ingredients are completely homeopathic and contain components not known ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The main categories of nutraceuticals and dietary supplements are vitamins, minerals, herbal medicines, probiotics, n -3 PUFA, antioxidants and polyphenol supplements. Some of the claims include memory enhancement ( 31 ) , maintenance of memory function ( 31 ) , and protection from cell degeneration ( 32 ) , whereas others suggest that nutraceuticals exhibit beneficial outcomes in certain conditions such as AD ( 33 ) . Nevertheless, the perception of efficacy in relation to the scientific literature available requires a systematic analysis and assessment.…”
mentioning
confidence: 99%
“…The main categories of nutraceuticals and dietary supplements are vitamins, minerals, herbal medicines, probiotics, n -3 PUFA, antioxidants and polyphenol supplements. Some of the claims include memory enhancement ( 31 ) , maintenance of memory function ( 31 ) , and protection from cell degeneration ( 32 ) , whereas others suggest that nutraceuticals exhibit beneficial outcomes in certain conditions such as AD ( 33 ) . Nevertheless, the perception of efficacy in relation to the scientific literature available requires a systematic analysis and assessment.…”
mentioning
confidence: 99%
“…Disturbances in glutamate and glutathione metabolism can lead to a series of neurologic phenotypes, including developmental delay, ataxia, seizures, and intellectual disability [ 35 ]. Moreover, 5-oxoproline was also developed and sold as an over-the-counter “smart drug” for cognitive and memory improvement [ 36 , 37 ]. However, it was also demonstrated that metabolic acidosis could be caused by excessive 5-oxoproline generation, with multiple adverse effects on many organ systems [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disturbances in glutamate and glutathione metabolism can lead to a series of neurologic phenotypes, including developmental delay, ataxia, seizures, and intellectual disability [34]. Moreover, 5-oxoproline was also developed and sold as an over-the-counter "smart drug" for cognitive and memory improvement [35,36]. However, it was also demonstrated that metabolic acidosis could be caused by excessive 5-oxoproline generation, with multiple adverse effects on many organ systems [37].…”
Section: Discussionmentioning
confidence: 99%